Peran Gamifikasi E-Commerce Untuk Mendukung Ekonomi Kreatif - Qurotul Aini; Mukti Budiarto; Aulia Edliyanti (UNIVERSITAS RAHARJA, 2021)
In accordance with Presidential Decree Number 142 of 2018 on Economic Development Master Plan 2018-2025 National Creative that serve as the foundation in developing a creative economy that supports the national policy on